Developing a Tool to Measure Person-Centered Care in Service Planning - Stanhope, Victoria; Baslock, Daniel; Tondora, Janis; Jessell, Lauren; Ross, Abigail M.; Marcus, Steven C. (Frontiers in Psychiatry, 2021)
Background: Delivering person-centered care is a key component of health care reform. Despite widespread endorsement, medical and behavioral health settings struggle to specify and measure person-centered care objectively. This study presents the validity and reliability of the Person-Centered Care Planning Assessment Measure (PCCP-AM), an objective measure of the extent to which service planning is person-centered. Methods: Based upon the recovery-oriented practice of person-centered care planning, the 10-item PCCP-AM tool rates service plans on the inclusion of service user strengths, personal life goals, natural supports, self-directed actions and the promotion of community integration. As part of a large randomized controlled trial of person-centered care planning, service plans completed by community mental health clinic providers were rated using the PCCP-AM. Reliability was tested by calculating inter-rater reliability across 168 plans and internal consistency across 798 plans. To test concurrent validity, PCCP-AM scores for 84 plans were compared to expert rater scores on a separate instrument.. Results: Interrater reliability for each of the 10 PCCP-AM items as measured by Kendall’s W ranged from W=.77 to W=.89 and percent of scores within +/-1 point of each other ranged from 85.7% to 100%. Overall internal consistency as measured by Cronbach’s alpha across 798 plans was = .72. Concurrent validity as measured byby Kendall’s W ranged from W=.55 to W=.74 and percent of item scores within +/-1 point of expert rater scores ranged from 73.8% to 86.8%. Conclusions: Findings demonstrated that the 10-item PCCP-AM was a valid and reliable objective measure of person-centered care. Using the service plan as an indicator of multiple domains of person-centered care, the measure provides a valuable tool to inform clinical supervision and quality improvement across programs. More psychometric testing is needed to strengthen the measure for research purposes.